Crowding Externalities from Tourist Use of Urban Space - Bart Neuts; Peter Nijkamp; Eveline van Leeuwen (Tinbergen Institute, 2013)
Popular urban tourist destinations are attracting large numbers of both overnight visitors and excursionists. Since urban cities perform a multitude of functions, the space requirements of tourists can, at times, interfere with those of local users. This paper addresses the issue of disutilities of space congestion through a dichotomous choice experiment model in order to offer a monetary valuation of tourist crowding in urban public space. A resident survey was carried out in the city of Amsterdam in order to estimate a random parameter logit model through which the residents' willingness to pay to avoid unfavourable crowding situations can be assessed. Their willingness to pay in order to increase the use levels by visitors in the Dam area from `not at all crowded' or `not crowded' to `crowded' was respectively exteuro1.36 and exteuro0.83 annually, while the mean willingness to pay for a decline in the use level from `very crowded' to `crowded' was estimated to be exteuro11.06 a year. While tourism is only partly responsible for these crowding levels, the results demonstrate that the social effects of tourist consumption can be positive as well as negative, depending on the existing use level and attitudinal perceptions of residents.
Keywords: P25; 330; public space; crowding; externalities; choice experiments; tourism; willingness to pay